Catalyst layer, catalyst layer forming liquid, and membrane electrode assembly

A catalyst layer with a carbon alloy catalyst and specific cyclic ether structures addresses the need for improved power generation efficiency in fuel cells by enhancing oxygen permeability and catalytic activity, resulting in better fuel cell performance.

JP7616077B2Active Publication Date: 2025-01-17AGC INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021567621
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-27
Filing Date
2020-12-24
Publication Date
2025-01-17
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

There is a need for further improvement in the power generation efficiency of fuel cells, particularly those using carbon alloy catalysts, to make them more efficient and cost-effective.

Method used

A catalyst layer containing a carbon alloy catalyst and a polymer with specific cyclic ether structures, which enhances oxygen permeability and catalytic activity, is developed to improve the power generation efficiency of fuel cells.

Benefits of technology

The catalyst layer achieves enhanced power generation efficiency in fuel cells by improving oxygen permeability and catalytic activity, leading to better performance and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616077000033
    Figure 0007616077000033
  • Figure 0007616077000001
    Figure 0007616077000001
  • Figure 0007616077000002
    Figure 0007616077000002
Patent Text Reader

Abstract

The present invention provides: a catalyst layer which enables the formation of a fuel cell that has excellent power generation efficiency; a liquid for forming a catalyst layer; and a membrane electrode assembly. A catalyst layer according to the present invention is characterized by comprising: a carbon alloy catalyst; and a polymer that has an ion exchange group, while having at least one unit containing a cyclic ether structure, said unit being selected from the group consisting of a unit represented by formula (u11), a unit represented by formula (u12), a unit represented by formula (u21), a unit represented by formula (u22) and a unit represented by formula (u24).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst layer, a liquid for forming a catalyst layer, and a membrane electrode assembly. [Background technology]

[0002] It is known that a membrane electrode assembly in a polymer electrolyte fuel cell has an anode and a cathode having a catalyst layer containing a catalyst and a polymer having an ion exchange group, and a solid polymer electrolyte membrane disposed between the anode and the cathode. As the catalyst contained in the catalyst layer, precious metals such as platinum and palladium, which have high oxygen reduction activity, and alloys containing them are widely used. However, precious metal catalysts have problems such as high cost and rare materials, so in order to widely disseminate fuel cells, technological development is being carried out on catalysts with significantly reduced platinum content or catalysts formed without using platinum. As one of these, a carbon catalyst has been proposed that has oxygen reduction activity in the carbonized material itself, and that exhibits high oxygen reduction activity without supporting expensive precious metals such as platinum or platinum alloys, or with the use of only a small amount of precious metal.As a method for producing this carbon catalyst, a method has been proposed in which an organic substance and a material containing a metal are mixed and carbonized to produce a carbon material (carbon alloy catalyst) with catalytic activity. Patent Document 1 discloses a catalyst layer containing a carbon alloy catalyst and Nafion (registered trademark), which is a polymer having an ion exchange group. It also discloses that the carbon alloy catalyst is obtained by mixing a thermosetting resin raw material (e.g., polyfurfuryl alcohol, furan resin, phenol resin, etc.) that produces non-graphitizable carbon with a metal compound (e.g., iron, cobalt, nickel, etc.), and carbonizing the mixture. Patent Document 2 discloses a method in which, instead of the thermosetting resin used in Patent Document 1, a thermoplastic resin such as polyvinyl chloride or polyvinyl alcohol is used, mixed with a metal compound containing at least one of Co and Fe, and carbon black is added. The thermoplastic resin is then oxidized in an oxygen-containing atmosphere to make it infusible, and after the infusibility process, the thermoplastic resin is carbonized by heat treatment at 800 to 1000°C to obtain a carbon alloy catalyst. Patent Document 3 discloses a fuel cell electrode (catalyst layer) based on carbon alloy fine particles doped with nitrogen atoms and / or boron atoms. Specifically, the document discloses a method for obtaining a carbon alloy catalyst doped with nitrogen atoms by thermally reacting a nitrogen-containing compound such as phthalocyanine as a carbon alloy catalyst with a precursor of a thermosetting resin such as furan resin to polymerize a nitrogen-containing thermosetting resin, and then heat-treating the obtained nitrogen-containing thermosetting resin at a temperature of 400 to 1500°C and pulverizing it. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2003-249231 A [Patent Document 2] International Publication No. 2015 / 147131 [Patent Document 3] JP 2004-362802 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, there has been a demand for further improvement in the power generation efficiency of fuel cells. The present inventors have evaluated a catalyst layer containing a carbon alloy catalyst as described in Patent Document 1 and found that there is room for improvement in the power generation efficiency of fuel cells.

[0005] In view of the above circumstances, an object of the present invention is to provide a catalyst layer, a catalyst layer forming liquid, and a membrane electrode assembly that can form a fuel cell with excellent power generation efficiency. [Means for solving the problem]

[0006] As a result of intensive research into the above-mentioned problems, the inventors have discovered that in a catalyst layer containing a carbon alloy catalyst and a polymer having an ion exchange group, if the polymer has a unit containing a specific cyclic ether structure, a fuel cell with excellent power generation efficiency can be obtained, and have arrived at the present invention.

[0007] That is, the present inventors have found that the above problems can be solved by the following configuration. [1] A catalyst layer comprising: a carbon alloy catalyst; and a polymer having an ion exchange group, the polymer having a unit containing at least one cyclic ether structure selected from the group consisting of a unit represented by formula (u11) described below, a unit represented by formula (u12) described below, a unit represented by formula (u21) described below, a unit represented by formula (u22) described below, and a unit represented by formula (u24) described below. In the formula (u11) below, R 11 is a divalent perfluoro organic group which may have an ether-bonded oxygen atom, and R 12 , R 13 , R 15 and R 16 each independently represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom or a fluorine atom; R 14 represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom, a fluorine atom, or -R 11 (SO2X(SO2R f ) a ) - M + It is a group represented by M + is H + , a monovalent metal cation or an ammonium ion in which one or more hydrogen atoms may be substituted by a hydrocarbon group; R fis a linear or branched perfluoroalkyl group which may have an ether-bonded oxygen atom, X is an oxygen atom, a nitrogen atom or a carbon atom, and when X is an oxygen atom, a=0, when X is a nitrogen atom, a=1, and when X is a carbon atom, a=2. In the formula (u12) below, R 21 is a perfluoroalkylene group having 1 to 6 carbon atoms or a perfluoroalkylene group having 2 to 6 carbon atoms and an ether-bonding oxygen atom between the carbon-carbon bonds, R 22 is a fluorine atom, a perfluoroalkyl group having 1 to 6 carbon atoms, a perfluoroalkyl group having 2 to 6 carbon atoms and an ether-bonded oxygen atom between the carbon-carbon bonds, or -R 21 (SO2X(SO2R f ) a ) - M + It is a group represented by M + , R f , X and a are as defined above. In the formula (u21) described below, R 41 , R 42 , R 43 , R 44 , R 45 and R 46 each independently represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom or a fluorine atom. In the formula (u22) described below, s is 0 or 1, R 51 and R 52 are each independently a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a spiro ring formed by linking together (when s is 0), and R 53 and R 54 are each independently a fluorine atom or a perfluoroalkyl group having 1 to 5 carbon atoms, and R 55 is a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a perfluoroalkoxy group having 1 to 5 carbon atoms. In the formula (u24) below, R 71 , R 72 , R 73 , R 74 , R 75 and R 76each independently represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom or a fluorine atom. [2] The catalyst layer according to [1], wherein the total content of the units containing the cyclic ether structure is 30 mol % or more based on all units contained in the polymer. [3] The catalyst layer according to [1] or [2], wherein the unit containing a cyclic ether structure contains a unit represented by formula (u22). [4] The catalyst layer according to any one of [1] to [3], wherein the polymer further has a unit based on a perfluoromonomer, and the unit based on the perfluoromonomer does not contain a cyclic ether structure and has an ion exchange group. [5] The catalyst layer of [4], wherein the unit based on the perfluoromonomer is a unit represented by formula (u32) described below. In the formula (u32) below, Q 1 is a perfluoroalkylene group which may have an ether-bonded oxygen atom, and Q 2 is a single bond or a perfluoroalkylene group which may have an ether-bonded oxygen atom, Y is a fluorine atom or a monovalent perfluoroorganic group, q is 0 or 1, R f is a linear or branched perfluoroalkyl group which may have an ether-bonded oxygen atom, X is an oxygen atom, a nitrogen atom or a carbon atom, and when X is an oxygen atom, a=0, when X is a nitrogen atom, a=1, and when X is a carbon atom, a=2. [6] The catalyst layer according to any one of [1] to [5], wherein the ion exchange capacity of the polymer is 1.1 to 2.8 meq / g dry resin. [7] The catalyst layer according to any one of [1] to [6], wherein the volumetric flow rate value of the polymer is 200 to 330°C. [8] A liquid for forming a catalyst layer, comprising: a carbon alloy catalyst; a polymer having a unit containing at least one cyclic ether structure selected from the group consisting of a unit represented by formula (u11) described below, a unit represented by formula (u12) described below, a unit represented by formula (u21) described below, a unit represented by formula (u22) described below, and a unit represented by formula (u24) described below, and having an ion exchange group; and a solvent. In the formula (u11) below, R 11 is a divalent perfluoro organic group which may have an ether-bonded oxygen atom, and R 12 , R 13 , R 15 and R 16 each independently represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom or a fluorine atom; R 14 represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom, a fluorine atom, or -R 11 (SO2X(SO2R f ) a ) - M + It is a group represented by M + is H + , a monovalent metal cation or an ammonium ion in which one or more hydrogen atoms may be substituted by a hydrocarbon group; R f is a linear or branched perfluoroalkyl group which may have an ether-bonded oxygen atom, X is an oxygen atom, a nitrogen atom or a carbon atom, and when X is an oxygen atom, a=0, when X is a nitrogen atom, a=1, and when X is a carbon atom, a=2. In the formula (u12) below, R 21 is a perfluoroalkylene group having 1 to 6 carbon atoms or a perfluoroalkylene group having 2 to 6 carbon atoms and an ether-bonding oxygen atom between the carbon-carbon bonds, R 22 is a fluorine atom, a perfluoroalkyl group having 1 to 6 carbon atoms, a perfluoroalkyl group having 2 to 6 carbon atoms and an ether-bonded oxygen atom between the carbon-carbon bonds, or -R 21 (SO2X(SO2R f ) a ) - M + It is a group represented by M + , R f , X and a are as defined above. In the formula (u21) described below, R 41 , R 42 , R 43 , R 44 , R 45 and R 46each independently represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom or a fluorine atom. In the formula (u22) described below, s is 0 or 1, R 51 and R 52 are each independently a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a spiro ring formed by linking together (when s is 0), and R 53 and R 54 are each independently a fluorine atom or a perfluoroalkyl group having 1 to 5 carbon atoms, and R 55 is a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a perfluoroalkoxy group having 1 to 5 carbon atoms. In the formula (u24) below, R 71 , R 72 , R 73 , R 74 , R 75 and R 76 each independently represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom or a fluorine atom. [9] The liquid for forming a catalyst layer according to [8], wherein the total content of the units containing the cyclic ether structure is 30 mol % or more based on all units contained in the polymer.

[10] The liquid for forming a catalyst layer according to [8] or [9], wherein the unit having a cyclic ether structure includes a unit represented by formula (u22).

[11] The liquid for forming a catalyst layer according to any of [8] to

[10] , wherein the polymer further has a unit based on a perfluoromonomer, the unit based on the perfluoromonomer not containing a cyclic ether structure and having an ion exchange group.

[12] The liquid for forming a catalyst layer according to

[11] , wherein the unit based on the perfluoromonomer is a unit represented by formula (u32) described below. In the formula (u32) below, Q 1 is a perfluoroalkylene group which may have an ether-bonded oxygen atom, and Q 2is a single bond or a perfluoroalkylene group which may have an ether-bonded oxygen atom, Y is a fluorine atom or a monovalent perfluoroorganic group, q is 0 or 1, R f is a linear or branched perfluoroalkyl group which may have an ether-bonded oxygen atom, X is an oxygen atom, a nitrogen atom or a carbon atom, and when X is an oxygen atom, a=0, when X is a nitrogen atom, a=1, and when X is a carbon atom, a=2.

[13] A membrane electrode assembly comprising: an anode having a catalyst layer; a cathode having a catalyst layer; and a solid polymer electrolyte membrane disposed between the anode and the cathode, wherein at least one of the catalyst layer of the anode and the catalyst layer of the cathode is a catalyst layer according to any one of [1] to [7].

[14] A membrane electrode assembly as described in

[13] , used in polymer electrolyte fuel cells. Effect of the Invention

[0008] According to the present invention, it is possible to provide a catalyst layer, a catalyst layer forming liquid, and a membrane electrode assembly that can form a fuel cell with excellent power generation efficiency. [Brief description of the drawings]

[0009] [Figure 1] 1 is a schematic cross-sectional view showing an example of a membrane electrode assembly of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The terms used in the present invention have the following meanings. A "unit" in a polymer means an atomic group derived from one molecule of a monomer formed by polymerization of the monomer. The unit may be an atomic group formed directly by a polymerization reaction, or may be an atomic group in which a part of the atomic group is converted into a different structure by treating the polymer obtained by the polymerization reaction. The content (mol %) of each unit relative to the total units contained in the polymer is determined by analyzing the polymer by nuclear magnetic resonance spectroscopy. The term "precursor group of an ion exchange group" refers to a group that can be converted into an ion exchange group by a hydrolysis treatment, an acidification treatment, or other treatment such as salt exchange with a metal cation. "TQ value" is the volumetric flow rate value of a polymer, and is determined by the method described in the Examples. The TQ value is an index of molecular weight. A numerical range expressed using "~" means that the range includes the numerical values ​​before and after "~" as the lower and upper limits.

[0011] The unit represented by the formula (u11) is written as unit (u11). The units represented by other formulas are written in the same way. Moreover, the monomer represented by the formula (m11) will be referred to as the monomer (m11). Monomers represented by other formulae will be similarly referred to. In addition, the group represented by formula (g1) will be referred to as group (g1). Groups represented by other formulae will be similarly referred to. A unit containing at least one cyclic ether structure selected from the group consisting of units (u11), (u12), (u21), (u22) and (u24) may be referred to as a “specific cyclic ether structural unit”. The monomer (m11), the monomer (m12), the monomer (m21), the monomer (m22) and the monomer (m24) may be collectively referred to as "specific cyclic monomers".

[0012] "Carbon alloy catalyst" means a catalyst using "carbon alloy." Here, "carbon alloy" is defined by the Carbon Society of Japan as "a material consisting of a multi-component system mainly composed of an aggregate of carbon atoms, which has physical and chemical interactions between its constituent units. However, carbons with different hybridization properties are considered to be different components." The definition of "carbon alloy" in this specification is the same.

[0013] [Catalyst layer] The catalyst layer of the present invention (hereinafter also referred to as "the catalyst layer") contains a carbon alloy catalyst and a polymer having a specific cyclic ether structural unit and an ion exchange group (hereinafter also referred to as polymer (H)). The use of this catalyst layer makes it possible to obtain a fuel cell with excellent power generation efficiency. Although the details of why this is the case are not clear, it is presumed to be due to the following reasons. Since the polymer (H) has a specific cyclic ether structural unit, it has higher oxygen permeability than Nafion (registered trademark, manufactured by DuPont). This is believed to improve the catalytic activity of the carbon alloy catalyst and the power generation efficiency of the fuel cell.

[0014] <Carbon alloy catalyst> As the carbon alloy catalyst, a known carbon alloy can be used. One example of such a carbon alloy is a carbon alloy (hereinafter also referred to as "carbon alloy C1") obtained by adding and mixing a metal to a raw material that produces non-graphitizable carbon, followed by carbonization by heat treatment, the carbon alloy having a nanoshell structure that includes at least a turbostratic structure in part, and containing non-graphitizable carbon as the main component.

[0015] Among the raw materials used in the production of carbon alloy C1, specific examples of raw materials that produce non-graphitizable carbon include furfuryl alcohol, furan resin, phenol resin, polyvinyl chloride, polyvinyl alcohol, and polyacrylonitrile. Two or more types of materials that produce non-graphitizable carbon may be used in combination. Specific examples of metals include transition metals classified into Groups 3 to 12 of the periodic table, and among these, manganese, iron, cobalt, nickel, copper, and chromium are preferred, with manganese, iron, and cobalt being particularly preferred. Two or more types of metals may be used in combination. The metal can be used as a simple metal or a compound containing the metal, and it is preferable to use a compound containing the metal. Specific examples of the compound containing the metal include metal salts, metal oxides, metal hydroxides, metal nitrides, metal sulfides, metal carbides, and metal complexes.

[0016] At least one of a compound containing a nitrogen atom and a compound containing a boron atom may be used as a raw material for producing the carbon alloy C1. This allows the carbon alloy C1 to be doped with at least one of a nitrogen atom and a boron atom. The performance of the carbon alloy C1 is improved when the carbon alloy C1 is doped with at least one of a nitrogen atom and a boron atom. Specific examples of the compound containing a nitrogen atom include phthalocyanine, acrylonitrile, ethylenediaminetetraacetic acid, and melamine. Specific examples of the compound containing a boron atom include a boron trifluoride methanol complex and a boron trifluoride tetrahydrofuran complex.

[0017] A specific example of carbonization by heat treatment is a method in which the raw material is heated at 300 to 1500°C.

[0018] As the carbon alloy C1, for example, the electrode catalyst described in JP 2003-249231 A, the fuel cell electrode catalyst described in JP 2005-019332 A, and the carbon alloy catalyst described in WO 2015 / 147131 can be used.

[0019] Another example of the carbon alloy is a carbon alloy (hereinafter also referred to as "carbon alloy C2") obtained by mixing and heating a thermosetting resin or its precursor with at least one of a compound containing a nitrogen atom and a compound containing a boron atom, followed by a carbonization treatment by heat treatment, and which improves the oxygen reduction activity of the catalyst layer due to structural defects and electron deficiencies in a crystal structure composed of carbon atoms.

[0020] Among the raw materials used in the production of the carbon alloy C2, specific examples of the thermosetting resin or its precursor include furfuryl alcohol, furan resin, and phenol resin. Two or more types of thermosetting resins may be used in combination. In addition, specific examples of the compound containing a nitrogen atom and the compound containing a boron atom are the same as the specific examples of the compound containing a nitrogen atom and the compound containing a boron atom shown as the raw material of the carbon alloy C1. Two or more kinds of the compound containing a nitrogen atom and the compound containing a boron atom may be used in combination. In the production of the carbon alloy C2, a specific example of the method of carbonization by heat treatment is the same as the method of carbonization by heat treatment in the production of the carbon alloy C1.

[0021] As the carbon alloy C2, for example, carbon alloy fine particles described in JP-A-2004-362802, WO-A-2006 / 003831, and JP-A-2007-311026 can be used.

[0022] As the carbon alloy catalyst, a carbon alloy catalyst available from GS Alliance Co., Ltd. may be used.

[0023] The carbon alloy catalyst may be supported on a carbon support. Specific examples of the carbon support include carbon black powder, graphitized carbon, carbon fiber, and carbon nanotubes. An example of a method for supporting a carbon alloy catalyst on a carbon support is a method in which a carbon support such as carbon black powder is added to the above-mentioned raw material for producing nanoshell-containing carbon (NSCC).

[0024] The catalyst layer may contain a catalyst other than the carbon alloy catalyst (hereinafter, also referred to as "other catalyst"). Examples of the other catalyst include precious metal catalysts, and platinum catalysts or platinum alloy catalysts are preferred from the viewpoint of excellent catalytic activity and stability.

[0025] <Polymer (H)> The polymer (H) is a polymer having an ion exchange group and has the following specific cyclic ether structural unit.

[0026] [ka]

[0027] In formula (u11), R 11 is a divalent perfluoro organic group which may have an ether bond oxygen atom. The organic group is a group having one or more carbon atoms. The divalent perfluoro organic group is preferably a perfluoroalkylene group. When the perfluoroalkylene group has an ether bond oxygen atom, the number of oxygen atoms may be one or more. In addition, the oxygen atom may be located between the carbon-carbon bonds of the perfluoroalkylene group, or may be located at the carbon atom bond end. The perfluoroalkylene group may be linear or branched, but is preferably linear. R 12 , R 13 , R 15 and R 16 are each independently a monovalent perfluoro organic group which may have an ether-bonded oxygen atom or a fluorine atom. As the monovalent perfluoro organic group, a perfluoroalkyl group is preferable. 15 and R 16 From the viewpoint of high polymerization reactivity, it is preferable that at least one of them is a fluorine atom, and it is more preferable that both of them are fluorine atoms. R 14 represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom, a fluorine atom, or -R 11 It is a group represented by SO2F. As the monovalent perfluoro organic group, a perfluoroalkyl group is preferable. When the perfluoroalkyl group has an ether-bonded oxygen atom, the number of oxygen atoms may be one or more. In addition, the oxygen atom may be located between the carbon-carbon bonds of the perfluoroalkyl group, or may be located at the carbon atom bond terminal. The perfluoroalkyl group may be linear or branched, but is preferably linear. In formula (u11), two R 11 If it contains two R 11 may be the same or different from each other. R 14represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom, a fluorine atom, or -R 11 (SO2X(SO2R f ) a ) - M + The monovalent perfluoro organic group is preferably a perfluoroalkyl group. When the perfluoroalkyl group has an ether-bonded oxygen atom, the number of oxygen atoms may be one or more. The oxygen atom may be located between the carbon-carbon bonds of the perfluoroalkyl group, or at the carbon atom bond terminal. The perfluoroalkyl group may be linear or branched, but is preferably linear. In formula (u11), two R 11 If it contains two R 11 may be the same or different from each other. M + is H + , a monovalent metal cation (e.g., potassium ion, sodium ion) or an ammonium ion in which one or more hydrogen atoms may be substituted with a hydrocarbon group (e.g., methyl group, ethyl group). From the viewpoint of high conductivity, H + is preferred. R f is a straight-chain or branched perfluoroalkyl group which may have an ether-bonded oxygen atom. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 8, and more preferably 1 to 6. Two or more R f If there are two or more R f may be the same or different from each other. X is an oxygen atom, a nitrogen atom, or a carbon atom, and when X is an oxygen atom, a=0; when X is a nitrogen atom, a=1; and when X is a carbon atom, a=2. -(SO2X(SO2R f ) a ) - M + Specific examples of groups include sulfonic acid groups (-SO3 - M + group), sulfonimide group (-SO2N(SO2R f ) - M+ group), or sulfonmethide group (-SO2C(SO2R f )2) - M + Groups such as

[0028] The unit (u11) is preferably the unit (u11-1).

[0029] [ka]

[0030] [ka]

[0031] In formula (u12), R 21 is a perfluoroalkylene group having 1 to 6 carbon atoms or a perfluoroalkylene group having 2 to 6 carbon atoms and having an ether-bonding oxygen atom between the carbon-carbon bonds. When the perfluoroalkylene group has an ether-bonding oxygen atom, the number of oxygen atoms may be 1 or 2 or more. The perfluoroalkylene group may be linear or branched, but is preferably linear. R 22 is a fluorine atom, a perfluoroalkyl group having 1 to 6 carbon atoms, a perfluoroalkyl group having 2 to 6 carbon atoms and an ether-bonded oxygen atom between the carbon-carbon bonds, or -R 21 (SO2X(SO2R f ) a ) - M + In the case where the perfluoroalkyl group has an ether-bonded oxygen atom, the number of oxygen atoms may be one or more. The perfluoroalkyl group may be linear or branched, but is preferably linear. In the formula (u12), two R 21 If it contains two R 21 may be the same or different from each other. M in formula (u12) + , R f, X and a are the M + , R f , X and a.

[0032] Specific examples of the unit (u12) include the unit (u12-1) and the unit (u12-2). + is M in equation (u11). + is synonymous with.

[0033] [ka]

[0034] [ka]

[0035] In formula (u21), R 41 , R 42 , R 43 , R 44 , R 45 and R 46 are each independently a monovalent perfluoro organic group which may have an ether-bonding oxygen atom or a fluorine atom. The monovalent perfluoro organic group is preferably a perfluoroalkyl group. When the perfluoroalkyl group has an ether-bonding oxygen atom, the number of oxygen atoms may be one or more. In addition, the oxygen atom may be located between the carbon-carbon bonds of the perfluoroalkyl group, or may be located at the carbon atom bond end. The perfluoroalkyl group may be linear or branched, but is preferably linear. R 45 and R 46 From the viewpoint of high polymerization reactivity, it is preferable that at least one of them is a fluorine atom, and it is particularly preferable that both of them are fluorine atoms.

[0036] The unit (u21) is preferably the unit (u21-1).

[0037] [ka]

[0038] [ka]

[0039] In formula (u22), s is 0 or 1, and 0 is preferable. R 51 and R 52 each independently represents a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a spiro ring formed by linking together (with the proviso that s is 0). R 53 and R 54 each independently represents a fluorine atom or a perfluoroalkyl group having 1 to 5 carbon atoms. R 55 R is a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a perfluoroalkoxy group having 1 to 5 carbon atoms. 55 is preferably a fluorine atom because of its high polymerization reactivity. The perfluoroalkyl group and the perfluoroalkoxy group may be linear or branched, but are preferably linear.

[0040] The unit (u22) is preferably the unit (u22-1).

[0041] [ka]

[0042] [ka]

[0043] In formula (u24), R 71 ~R 76are each independently a monovalent perfluoro organic group which may have an ether-bonding oxygen atom or a fluorine atom. The monovalent perfluoro organic group is preferably a perfluoroalkyl group. When the perfluoroalkyl group has an ether-bonding oxygen atom, the number of oxygen atoms may be one or more. In addition, the oxygen atom may be inserted between the carbon-carbon bond of the perfluoroalkyl group, or may be inserted at the carbon atom bond end. The perfluoroalkyl group may be linear or branched, but is preferably linear. R 71 ~R 74 is preferably a fluorine atom because of its high polymerization reactivity.

[0044] The total content of the specific cyclic ether structural units is preferably 30 mol % or more, more preferably 40 mol % or more, and particularly preferably 65 mol % or more, based on the total units contained in the polymer (H), in order to obtain a more excellent power generation efficiency of the fuel cell. The upper limit of the total content of the specific cyclic ether structural units is preferably 100 mol %, particularly preferably 80 mol %, based on all units contained in the polymer (H). The polymer (H) may contain only one type of specific cyclic ether structural unit, or may contain two or more types. When two or more types are contained, the above content means the total amount thereof.

[0045] The polymer (H) may further have a unit based on a perfluoromonomer. However, the unit based on the perfluoromonomer does not contain a cyclic ether structure and has a unit having an ion exchange group. Hereinafter, such a unit is simply referred to as "a unit based on a perfluoromonomer". Examples of the unit based on a perfluoromonomer include the unit (u31) and the unit (u32), and the unit (u32) is preferred in terms of better power generation efficiency of the fuel cell.

[0046] [ka]

[0047] In the above formula, Z is a fluorine atom or a trifluoromethyl group, q is 0 or 1, m is an integer of 0 to 3, p is 0 or 1, n is an integer of 1 to 12, and m+p>0. M + is the M in the above formula (u11). + is synonymous with.

[0048] [ka]

[0049] Q 1 is a perfluoroalkylene group which may have an ether-bonding oxygen atom. Q 2 is a single bond or a perfluoroalkylene group which may have an ether-bonded oxygen atom. Q 1 and Q 2 When the perfluoroalkylene group has an ether-bonding oxygen atom, the number of oxygen atoms may be 1 or 2 or more. In addition, the oxygen atom may be located between the carbon atom-carbon atom bonds of the perfluoroalkylene group, or may be located at the end of the carbon atom bond. The perfluoroalkylene group may be linear or branched, but is preferably linear. The carbon number of the perfluoroalkylene group is preferably 1 to 6, particularly preferably 1 to 4. When the carbon number is 6 or less, the boiling point of the raw material fluorine-containing monomer is low, and distillation purification is easy. In addition, when the carbon number is 6 or less, the decrease in the ion exchange capacity of the polymer (H) is suppressed, and the proton conductivity is good.

[0050] Q 2 is preferably a perfluoroalkylene group which may have an ether-bonding oxygen atom, and more preferably a perfluoroalkylene group having 1 to 6 carbon atoms which may have an ether-bonding oxygen atom. 2 is a perfluoroalkylene group which may have an ether-bonded oxygen atom, Q 2is a single bond, the stability of power generation performance is excellent when the fuel cell is operated for a long period of time. Q 1 and Q 2 At least one of the groups is preferably a perfluoroalkylene group having 1 to 6 carbon atoms and an ethereal oxygen atom. A monomer having a perfluoroalkylene group having 1 to 6 carbon atoms and an ethereal oxygen atom can be synthesized without going through a fluorination reaction with fluorine gas, and therefore the yield is good and the production is easy.

[0051] Y is a fluorine atom or a monovalent perfluoro organic group. Y is preferably a fluorine atom or a linear perfluoroalkyl group having 1 to 6 carbon atoms which may have an etheric oxygen atom. q is 0 or 1. R f , X and a are R in the above formula (u11), f , X and a.

[0052] As the unit (u32), the units (u32-1) to (u32-3) are preferred, and the unit (u32-1) is particularly preferred, since they are easy to produce and easy to implement industrially.

[0053] [ka]

[0054] The total content of units based on perfluoromonomers is preferably 5 to 40 mol %, more preferably 10 to 35 mol %, and particularly preferably 15 to 30 mol %, based on all units contained in polymer (H), from the viewpoint of achieving a balance between battery output and mechanical strength and thus achieving better overall battery performance. The polymer (H) may contain only one type of unit based on a perfluoromonomer, or may contain two or more types. When two or more types are contained, the above content means the total amount thereof.

[0055] The polymer (H) may further contain units based on tetrafluoroethylene (TFE), which imparts water repellency and increases the water discharge ability in the catalyst layer, thereby improving the power generation efficiency of the fuel cell. The content of the units based on TFE is preferably from 5 to 40 mol %, more preferably from 5 to 35 mol %, and particularly preferably from 5 to 30 mol %, based on all the units contained in the polymer (H).

[0056] The polymer (H) may contain units other than those described above. Specific examples of such units include units based on monomers such as perfluoro(3-butenyl vinyl ether), perfluoro(allyl vinyl ether), perfluoro α-olefins (hexafluoropropylene, etc.), and perfluoro(alkyl vinyl ethers).

[0057] The ion exchange group contained in the polymer (H) is preferably the group (g1).

[0058] -(SO2X(SO2R f ) a ) - M + (g1)

[0059] M + , R f , X and a are each M in the above formula (u11). + , R f , X and a. Specific examples of the group (g1) include a sulfonic acid group (-SO3 - M + group), sulfonimide group (-SO2N(SO2R f ) - M + group), or sulfonmethide group (-SO2C(SO2R f )2) - M + group), and sulfonic acid group (-SO3 - M + Groups) are preferred. Polymer (H) is a polymer having an ion exchange group. When the specific cyclic ether structural unit in polymer (H) has an ion exchange group, it is not necessary for polymer (H) to have other units having an ion exchange group. When the specific cyclic ether structural unit in polymer (H) does not have an ion exchange group, polymer (H) must have a unit having an ion exchange group, such as a unit based on a perfluoromonomer.

[0060] A preferred embodiment of the polymer (H) is one containing units (u22) since this provides better power generation efficiency in a fuel cell. A more preferred embodiment of the polymer (H) is one containing units (u22) and units (u32), since this provides particularly excellent power generation efficiency for the fuel cell.

[0061] In the catalyst layer, the content of the polymer (H) is preferably 40 to 200 parts by mass, more preferably 60 to 140 parts by mass, and particularly preferably 75 to 100 parts by mass, per 100 parts by mass of the carbon alloy catalyst. When the content of the polymer (H) is within the above range, the power generation efficiency of the fuel cell is further improved. In addition, when the catalyst layer contains the above-mentioned other catalysts, the content of the above polymer (H) does not mean the value relative to the total amount of the carbon alloy catalyst and the other catalysts, but means the value relative to the content of the carbon alloy catalyst only.

[0062] (Physical Properties) The ion exchange capacity of the polymer (H) is preferably 1.1 to 2.8 milliequivalents / g dry resin, more preferably 1.2 to 2.8 milliequivalents / g dry resin, further preferably 1.3 to 2.3 milliequivalents / g dry resin, and particularly preferably 1.3 to 2.0 milliequivalents / g dry resin. If the ion exchange capacity is 1.1 milliequivalents / g dry resin or more, the conductivity of the polymer (H) is high, so that sufficient cell output can be obtained when used as a polymer for the catalyst layer of a fuel cell. If the ion exchange capacity is 2.8 milliequivalents / g dry resin or less, the synthesis of the polymer is easy. The TQ value of the polymer (H) is preferably 200 to 330° C. The lower limit of the TQ value is more preferably 210° C. from the viewpoint of preventing cracking of the electrode. The upper limit of the TQ value is more preferably 310° C. from the viewpoint of preventing thermal decomposition of the fluororesin, and is particularly preferably 300° C. or less. If the TQ value is within this range, the polymer (H) also has excellent hot water resistance.

[0063] (Method for producing polymer (H)) The polymer (H) is produced, for example, by converting a precursor group of the ion exchange group of the polymer (F) obtained by polymerizing a specific cyclic monomer and at least one of a perfluoromonomer and tetrafluoroethylene, which is used as necessary, into an ion exchange group. Each monomer that can be used in the production of the polymer (H) will be described below.

[0064] The unit (u11) is obtained by polymerizing the monomer (m11), and preferred embodiments of the monomer (m11) include the monomers (m11-1) to (m11-4). The monomer (m11) can be synthesized by a known method. In formula (m11), R 11 ~R 16 are the R in equation (u11), 11 ~R 16 is synonymous with.

[0065] [ka]

[0066] The unit (u12) is obtained by polymerizing the monomer (m12), and preferred embodiments of the monomer (m12) include the monomers (m12-1) and (m12-2). The monomer (m12) can be synthesized by a known method. R in formula (m12) 21 and R 22 are the R in equation (u12), 21 and R 22 is synonymous with.

[0067] [ka]

[0068] The unit (u21) is obtained by polymerizing the monomer (m21), and preferred embodiments of the monomer (m21) include the monomers (m21-1) and (m21-2). The monomer (m21) can be synthesized by a known method. R in formula (m21) 41 ~R 46 are R in equation (u21), 41 ~R 46 is synonymous with.

[0069] [ka]

[0070] The unit (u22) is obtained by polymerizing the monomer (m22), and preferred embodiments of the monomer (m22) include the monomers (m22-1) to (m22-11). The monomer (m22) can be synthesized by a known method. R in formula (m22) 51 ~R 55 and s are R in formula (u22), 51 ~R 55 and s.

[0071] [ka]

[0072] The unit (u24) is obtained by cyclopolymerizing the monomer (m24), and preferred embodiments of the monomer (m24) include the monomers (m24-1) to (m24-3). The monomer (m24) can be synthesized by a known method. R in formula (m24) 71 ~R 76 are R in equation (u24), 71 ~R 76 is synonymous with.

[0073] CF(R 71 )=C(R 73 )-O-CF(R 76 )-CF(R 75 )-C(R 74 )=CF(R 72 ) (m24) CF2=CF-O-CF2-CF2-CF=CF2(m24-1) CF2=CF-O-CF2-CF(CF3)-CF=CF2(m24-2) CF2=CF-O-CF(CF3)-CF2-CF=CF2(m24-3)

[0074] For the production of the polymer (H), a perfluoromonomer not containing a cyclic ether structure but containing a precursor group of an ion exchange group may be used. Examples of the perfluoromonomer include the monomer (m31) and the monomer (m32), and the monomer (m32) is preferred from the viewpoint of achieving superior power generation efficiency in the fuel cell.

[0075] CF2=CF(CF2) q (OCF2CFZ) m O p (CF2) n SO2F (m31)

[0076] The monomer (m31) corresponds to the unit (u31). Z, q, m, p and n in the monomer (m31) have the same meanings as Z, q, m, p and n in the formula (u31), respectively.

[0077] The monomer (m31) is preferably the monomers (m31-1) to (m31-4). CF2 = CFO(CF2) n1 SO2F (m31-1) CF2 = CFOCF2CF(CF3)O(CF2) n2 SO2F (m31-2) CF2=CF(OCF2CF(CF3)) m3 O(CF2) n3 SO2F (m31-3) CF2 = CFCF2O(CF2) n4 SO2F (m31-4) Here, n1, n2, n3, and n4 are integers from 1 to 8, and m3 is an integer from 1 to 3.

[0078] The monomer (m31) can be synthesized, for example, by the method described in Prog. Polym. Sci., Vol. 12, 1986, p. 233-237; US Pat. No. 4,330,654, and the like.

[0079] [ka]

[0080] Monomer (m32) Q 1 , Q 2 , Y and q are the Q 1 , Q 2 , Y and q.

[0081] The monomer (m32) corresponds to the unit (u32). As the monomer (m32), the polymer (H) can be easily produced and the production can be easily carried out industrially. Therefore, the monomers (m32-1) to (m32-3) are preferred, and the monomer (m32-1) is particularly preferred.

[0082] [ka]

[0083] The monomer (m32) can be synthesized, for example, by the method described in WO 2007 / 013533, JP 2008-202039 A, and the like.

[0084] Tetrafluoroethylene may be used in the production of polymer (H).

[0085] Monomers other than those mentioned above may be used in the production of polymer (H). Specific examples of such monomers include perfluoro(3-butenyl vinyl ether), perfluoro(allyl vinyl ether), perfluoro α-olefins (such as hexafluoropropylene), and perfluoro(alkyl vinyl ethers).

[0086] An example of a method for converting a precursor group (-SO2F) of an ion exchange group into an ion exchange group is shown below. The group represented by -SO2F is a sulfonic acid group (-SO3 - H + The method for converting the group represented by -SO2F into a sulfonimide group (-SO2N(SO2R f ) - H + ) the following method (ii) can be mentioned. (i) A method in which a group represented by -SO2F is hydrolyzed to a sulfonate salt, and the sulfonate salt is converted to an acid form to convert it into a sulfonic acid group. (ii) A method in which a group represented by -SO2F is imidized to form a salt-type sulfonimide group, and then further converted to an acid-type sulfonimide group by acidification.

[0087] Method (i): The hydrolysis is carried out, for example, by contacting a polymer having a precursor of an ion exchange group with a basic compound in a solvent. Examples of the basic compound include sodium hydroxide and potassium hydroxide. Examples of the solvent include water and a mixed solvent of water and a polar solvent. Examples of the polar solvent include alcohol (methanol, ethanol, etc.) and dimethyl sulfoxide. The conversion to an acid form is carried out, for example, by contacting the polymer having a sulfonate with an aqueous solution of hydrochloric acid, sulfuric acid or the like. The hydrolysis and conversion to an acid form are usually carried out at 0 to 120°C.

[0088] Method (ii): The imidization can be carried out by the following methods. (ii-1) A group represented by -SO2F and Rf How to react with SO2NHM. (ii-2) In the presence of an alkali metal hydroxide, an alkali metal carbonate, MF, ammonia or a primary to tertiary amine, a group represented by -SO2F and R f How to react with SO2NH2. (ii-3) A group represented by -SO2F and R f A method of reacting with SO2NMSi(CH3)3. Here, M is an alkali metal or primary to quaternary ammonium. The conversion to an acid form is carried out by treating a polymer having a salt form of sulfonimide group with an acid (sulfuric acid, nitric acid, hydrochloric acid, etc.).

[0089] The polymer (H) in which the ion exchange group is a sulfonimide group can also be produced by polymerizing a monomer in which the group represented by -SO2F in the monomer (m11), (m12), (m31) or (m32) has been converted to a sulfonimide group, together with the monomer (m21) or (m22). A monomer in which the group represented by -SO2F has been converted into a sulfonimide group can be produced by adding chlorine or bromine to the carbon-carbon double bond of monomer (m11), (m12), (m31) or (m32), converting the group represented by -SO2F into a sulfonimide group by the method (ii), and then carrying out a dechlorination or debromination reaction using metallic zinc.

[0090] <Application> This catalyst layer is suitably used as a catalyst layer in a membrane electrode assembly described below.

[0091] [Catalyst layer forming liquid] The catalyst layer forming liquid of the present invention (hereinafter also referred to as "the catalyst layer forming liquid") contains a carbon alloy catalyst, a polymer (polymer (H)) having a specific cyclic ether structural unit and an ion exchange group, and a solvent. The carbon alloy catalyst and polymer (H) contained in the present catalyst layer forming liquid are the same as the carbon alloy catalyst and polymer (H) in the present catalyst layer described above, and therefore a description thereof will be omitted. The present catalyst layer can be formed by using the present catalyst layer forming liquid. A conventionally known method may be used to form a catalyst layer using the present catalyst layer forming liquid.

[0092] The solvent includes water and organic solvents, and may be a mixture of these. Specific examples of organic solvents include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-methyl-1-propanol, 2-butanol, 2-methyl-2-propanol, 2,2,2-trifluoroethanol, 2,2,3,3,3-pentafluoro-1-propanol, 2,2,3,3-tetrafluoro-1-propanol, 4,4,5,5,5-pentafluoro-1-pentanol, 1,1,1,3,3,3-hexafluoro-2-propanol, 3,3,3-trifluoro-1-propanol, 3,3,4,4,5,5,6,6,6-nonafluoro-1-hexanol, and 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluoro-1-octanol. The organic solvents may be used alone or in combination of two or more.

[0093] The solid content by mass of the present catalyst layer forming liquid is preferably 15 to 45 mass %, more preferably 20 to 35 mass %, particularly preferably 20 to 30 mass %, based on the total mass of the present catalyst layer forming liquid. The solid content mass of the present catalyst layer forming liquid means the mass of the present catalyst layer forming liquid after removing the solvent.

[0094] [Membrane electrode assembly] The membrane electrode assembly of the present invention comprises an anode having a catalyst layer, a cathode having a catalyst layer, and a solid polymer electrolyte membrane disposed between the anode and the cathode, and at least one of the catalyst layer of the anode and the catalyst layer of the cathode is the present catalyst layer described above. The membrane electrode assembly is suitable for use in a polymer electrolyte fuel cell. According to the membrane electrode assembly of the present invention, since it has the above-mentioned present catalyst layer, it is possible to form a fuel cell with excellent power generation efficiency.

[0095] 1 is a schematic cross-sectional view showing an example of a membrane electrode assembly of the present invention. The membrane electrode assembly 10 has an anode 13 having a catalyst layer 11 and a gas diffusion layer 12, a cathode 14 having the catalyst layer 11 and the gas diffusion layer 12, and a solid polymer electrolyte membrane 15 disposed between the anode 13 and the cathode 14 in contact with the catalyst layer 11.

[0096] At least one of the catalyst layer 11 of the anode 13 and the catalyst layer 11 of the cathode 14 may be the above-mentioned present catalyst layer, and both may be the above-mentioned catalyst layer. When one catalyst layer 11 is the above-mentioned present catalyst layer and the other catalyst layer 12 is a catalyst layer other than the above-mentioned present catalyst layer, a known catalyst layer may be used as the catalyst layer other than the present catalyst layer.

[0097] The catalyst layer 11 can be formed by the following method. (i) A method in which a catalyst layer forming liquid is applied onto the solid polymer electrolyte membrane 15, the gas diffusion layer 12, or a carbon layer (not shown) described below, and then dried. (ii) A method in which a catalyst layer forming liquid is applied onto a substrate film, dried to form a catalyst layer 11, and the catalyst layer 11 is transferred onto a solid polymer electrolyte membrane 15.

[0098] The gas diffusion layer 12 has a function of diffusing gas uniformly in the catalyst layer 11 and also functions as a current collector. Examples of the gas diffusion layer 12 include carbon paper, carbon cloth, carbon felt, etc. The gas diffusion layer 12 is preferably treated with polytetrafluoroethylene or the like to be water repellent. Although the membrane electrode assembly 10 in FIG. 1 includes a gas diffusion layer 12, the gas diffusion layer is an optional member and does not necessarily have to be included in the membrane electrode assembly.

[0099] The solid polymer electrolyte membrane 15 is a membrane containing a polymer having an ion exchange group. Examples of the polymer having an ion exchange group include the above-mentioned polymer (H) and a polymer having a known ion exchange group.Specific examples of the polymer having a known ion exchange group include a polymer having a unit based on monomer (m31) and a unit based on tetrafluoroethylene, in which the group represented by -SO2F is converted to a sulfonic acid group, and a polymer having a unit based on monomer (m32) and a unit based on tetrafluoroethylene, in which the group represented by -SO2F is converted to a sulfonic acid group.

[0100] The solid polymer electrolyte membrane 15 can be formed, for example, by a method (casting method) in which a liquid composition of a polymer is applied onto the substrate film or catalyst layer 11 and then dried. The liquid composition is a dispersion in which a polymer is dispersed in a solvent containing at least one of an organic solvent and water.

[0101] It is preferable to carry out a heat treatment in order to stabilize the solid polymer electrolyte membrane 15. The heat treatment temperature is preferably 130 to 200° C., although it depends on the type of polymer. The solid polymer electrolyte membrane 15 may be treated with hydrogen peroxide water as necessary.

[0102] The solid polymer electrolyte membrane 15 may be reinforced with a reinforcing material. Examples of the reinforcing material include a porous body, a fiber, a woven fabric, a nonwoven fabric, etc. Examples of the material for the reinforcing material include polytetrafluoroethylene, a tetrafluoroethylene-hexafluoropropylene copolymer, a tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer, polyethylene, polypropylene, polyphenylene sulfide, etc.

[0103] In order to further improve durability, the solid polymer electrolyte membrane 15 may contain one or more atoms selected from the group consisting of cerium and manganese. Cerium and manganese decompose hydrogen peroxide, which is a substance that causes deterioration of the solid polymer electrolyte membrane 15. Cerium and manganese are preferably present as ions in the solid polymer electrolyte membrane 15, and may be present in any state in the solid polymer electrolyte membrane 15 as long as they are present as ions. The solid polymer electrolyte membrane 15 may contain silica or heteropolyacid (zirconium phosphate, phosphomolybdic acid, phosphotungstic acid, etc.) as a water retention agent to prevent drying.

[0104] The membrane electrode assembly 10 is produced, for example, by the following method. (i) A method in which a catalyst layer 11 is formed on a solid polymer electrolyte membrane 15 to form a membrane catalyst layer assembly, and the membrane catalyst layer assembly is sandwiched between gas diffusion layers 12. (ii) A method in which a catalyst layer 11 is formed on a gas diffusion layer 12 to form electrodes (anode 13, cathode 14), and a solid polymer electrolyte membrane 15 is sandwiched between the electrodes.

[0105] The membrane electrode assembly 10 may have a carbon layer (not shown) between the catalyst layer 11 and the gas diffusion layer 12. By disposing the carbon layer, the gas diffusion property of the surface of the catalyst layer 11 is improved, and the power generation performance of the fuel cell can be further improved. The carbon layer contains, for example, carbon and a non-ionic fluorine-containing polymer. A specific example of the carbon is preferably a carbon nanofiber having a fiber diameter of 1 to 1000 nm and a fiber length of 1000 μm or less. A specific example of the non-ionic fluorine-containing polymer is polytetrafluoroethylene. EXAMPLES

[0106] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. Examples 1 to 11 are preparation examples, Examples 12 to 21 are working examples, and Example 22 is a comparative example.

[0107] [Ion exchange capacity] The ion exchange capacity of the polymer (H) (polymer after hydrolysis treatment) was determined by the following method. The polymer (H) was placed in a glove box and left in an atmosphere of dry nitrogen for 24 hours or more to dry it. The dry mass of the polymer (H) was measured in the glove box. Polymer (H) was immersed in a 2 mol / L aqueous sodium chloride solution, left at 60° C. for 1 hour, and then cooled to room temperature. The aqueous sodium chloride solution in which polymer (H) had been immersed was titrated with a 0.5 mol / L aqueous sodium hydroxide solution to determine the ion exchange capacity of polymer (H).

[0108] [TQ value] Using a flow tester (Shimadzu Corporation, CFT-500D) equipped with a nozzle having a length of 1 mm and an inner diameter of 1 mm, polymer (H) was melt-extruded while changing the temperature under the condition of an extrusion pressure of 2.94 MPa (gauge pressure). The extrusion amount of polymer (H) was measured by changing the temperature. 3 The temperature at which the TQ value was reached was calculated as the TQ value.

[0109] [Synthesis of monomer (m11-1)] A monomer (m11-1) was synthesized according to the method described in the Examples on pages 37-42 of WO 2003 / 037885.

[0110] [ka]

[0111] [Synthesis of monomer (m12-1)] A monomer (m12-1) was synthesized according to the method described in Example 1 of JP-A-2006-152249.

[0112] [ka]

[0113] [Synthesis of monomer (m31-4)] The monomer (m31-4) was synthesized by a known method.

[0114] [ka]

[0115] [Synthesis of monomer (m31-5)] The monomer (m31-5) was synthesized by a known method. CF2=CFOCF2CF2SO2F (m31-5)

[0116] [Synthesis of monomer (m32-1)] A monomer (m32-1) was synthesized according to the method described in Example 1 of JP-A-2008-202039.

[0117] [ka]

[0118] [Synthesis of monomer (m21-1)] The monomer (m21-1) was synthesized according to a known method.

[0119] [ka]

[0120] [Synthesis of monomer (m22-1)] The monomer (m22-1) was synthesized according to a known method.

[0121] [ka]

[0122] [Synthesis of monomer (m24-1)] The monomer (m24-1) was synthesized according to a known method.

[0123] [ka]

[0124] [Radical polymerization initiator] As radical polymerization initiators, the following compounds (i-1) to (i-3) were prepared.

[0125] <Compound (i-1)>

[0126] [ka]

[0127] <Compound (i-2)> ((CH3)2CHOCOO)2(i-2)

[0128] <Compound (i-3)> (C3F7COO)2(i-3)

[0129] [solvent] As a solvent, the following compounds (s-1) and (s-2) were prepared.

[0130] <Compound (s-1)> CClF2CF2CHClF (s-1)

[0131] <Compound (s-2)> CH3CCl2F (s-2)

[0132] [Production of mixture containing carbon alloy catalyst] A mixture A of carbon alloy catalyst and carbon black in Sample 1 of Experiment 2 of WO 2015 / 147131 was obtained.

[0133] [Example 1: Preparation example] 9.15g of monomer (m22-1), 45.65g of monomer (m32-1) and 6.4mg of compound (i-2) were charged into a 125mL stainless steel autoclave, and thoroughly degassed under cooling with liquid nitrogen. After that, the temperature was raised to 40°C and maintained for 24.5 hours, and the autoclave was cooled to stop the reaction. The product was diluted with compound (s-1), n-hexane was added thereto, the polymer was coagulated, and the mixture was filtered. The polymer was then stirred in compound (s-1), re-coagulated with n-hexane, and dried under reduced pressure at 80°C overnight to obtain polymer (F-1). The yield was 4.5 g.

[0134] The polymer (F-1) was immersed in an aqueous solution containing 20% ​​by mass of methanol and 15% by mass of potassium hydroxide at 50°C for 40 hours, whereby the -SO2F groups in the polymer (F-1) were hydrolyzed and converted to -SO3K groups. The polymer was then immersed in a 3 mol / L aqueous hydrochloric acid solution at room temperature for 2 hours. The aqueous hydrochloric acid solution was replaced, and the same treatment was repeated four more times to obtain a polymer (H-1) in which the -SO3K groups in the polymer were converted to sulfonic acid groups. The polymer (H-1) was thoroughly washed with ultrapure water. The ion exchange capacity of the polymer (H-1) was measured. The results are shown in Table 1.

[0135] A mixed solvent of ethanol and water (ethanol / water = 60 / 40 mass ratio) was added to the polymer (H-1) to adjust the solid concentration to 15 mass%, and the mixture was stirred at 105°C for 8 hours using an autoclave to obtain a liquid composition (D-1) in which the polymer (H-1) was dispersed in the dispersion medium.

[0136] [Example 2: Preparation example] In a 230mL stainless steel autoclave, 32.4g of monomer (m22-1), 166.70g of monomer (m32-1) and 101mg of compound (i-2) were charged and thoroughly degassed under cooling with liquid nitrogen. Then, 3.87g of tetrafluoroethylene (TFE) was charged, the temperature was raised to 24°C, and the mixture was stirred for 24 hours, after which the autoclave was cooled to stop the reaction. The product was diluted with compound (s-1), n-hexane was added thereto, the polymer was coagulated, and the mixture was filtered. The polymer was then stirred in compound (s-1), re-coagulated with n-hexane, and dried under reduced pressure at 80°C overnight to obtain polymer (F-2). The yield was 45.9 g. Polymer (H-2) was obtained from polymer (F-2) in the same manner as in Example 1. The ion exchange capacity of polymer (H-2) was measured. The results are shown in Table 1. A liquid composition (D-2) was obtained in the same manner as in Example 1 using the polymer (H-2).

[0137] [Example 3: Preparation example] In a 230mL stainless steel autoclave, 37.45g of monomer (m22-1), 120.20g of monomer (m32-1) and 25.2mg of compound (i-2) were charged and thoroughly degassed under cooling with liquid nitrogen. Then, 4.39g of TFE was charged, the temperature was raised to 24°C, and the mixture was stirred for 12 hours and 30 minutes, after which the autoclave was cooled to stop the reaction. The product was diluted with compound (s-1), n-hexane was added thereto, the polymer was coagulated, and the mixture was filtered. The polymer was then stirred in compound (s-1), re-coagulated with n-hexane, and dried under reduced pressure at 80°C overnight to obtain polymer (F-3). The yield was 29.6 g. Polymer (H-3) was obtained using polymer (F-3) in the same manner as in Example 1. The ion exchange capacity of polymer (H-3) was measured. The results are shown in Table 1. A liquid composition (D-3) was obtained in the same manner as in Example 1 using the polymer (H-3).

[0138] [Example 4: Preparation example] In a 125mL stainless steel autoclave, 8.50g of monomer (m22-1), 59.5g of monomer (m31-4) and 20.4mg of compound (i-2) were charged and thoroughly degassed under cooling with liquid nitrogen. Then, 2.5g of TFE was charged, the temperature was raised to 24°C, and the mixture was stirred for 24 hours, after which the autoclave was cooled to stop the reaction. The product was diluted with compound (s-1), n-hexane was added thereto, the polymer was coagulated, and the mixture was filtered. The polymer was then stirred in compound (s-1), re-coagulated with n-hexane, and dried under reduced pressure at 80°C overnight to obtain polymer (F-4). The yield was 11.1 g. Polymer (H-4) was obtained using polymer (F-4) in the same manner as in Example 1. The ion exchange capacity of polymer (H-4) was measured. The results are shown in Table 1. A liquid composition (D-4) was obtained in the same manner as in Example 1 using the polymer (H-4).

[0139] [Example 5: Preparation example] 9.80g of monomer (m22-1), 37.4g of monomer (m31-5) and 14.1mg of compound (i-2) were charged into a 125mL stainless steel autoclave, and thoroughly degassed under cooling with liquid nitrogen. Then, 2.5g of TFE was charged, the temperature was raised to 24°C, and the mixture was stirred for 24 hours, after which the autoclave was cooled to stop the reaction. The product was diluted with compound (s-1), n-hexane was added thereto, the polymer was coagulated, and the mixture was filtered. The polymer was then stirred in compound (s-1), re-coagulated with n-hexane, and dried under reduced pressure at 80°C overnight to obtain polymer (F-5). The yield was 10.5 g. Polymer (H-5) was obtained using polymer (F-5) in the same manner as in Example 1. The ion exchange capacity of polymer (H-5) was measured. The results are shown in Table 1. A liquid composition (D-5) was obtained in the same manner as in Example 1 using the polymer (H-5).

[0140] [Example 6: Preparation example] 3.5g of monomer (m21-1), 76.33g of monomer (m32-1) and 8.5mg of compound (i-2) were charged into a 125mL stainless steel autoclave and thoroughly degassed under cooling with liquid nitrogen. After that, the temperature was raised to 40°C and stirred for 24 hours, and the autoclave was cooled to stop the reaction. The product was diluted with compound (s-1), and n-hexane was added to it to coagulate the polymer and filter it. The polymer was then stirred in compound (s-1), re-coagulated with n-hexane, and dried under reduced pressure at 80°C overnight to obtain polymer (F-6). The yield was 6.4g. The density of polymer (F-6) was measured. The results are shown in Table 1. Using the polymer (F-6), a polymer (H-6) and a liquid composition (D-6) were obtained in the same manner as in Example 1. The ion exchange capacity of the polymer (H-6) was measured. The results are shown in Table 1.

[0141] [Example 7: Preparation example] In a 125mL stainless steel autoclave, 5.97g of monomer (m11-1), 13.70g of monomer (m22-1), 13.75g of compound (s-1) and 17.1mg of compound (i-1) were charged and thoroughly degassed under cooling with liquid nitrogen. After that, the temperature was raised to 65°C and maintained for 6 hours, and the autoclave was cooled to stop the reaction. The product was diluted with compound (s-1), n-hexane was added thereto, the polymer was coagulated, and the mixture was filtered. The polymer was then stirred in compound (s-1), re-coagulated with n-hexane, and dried under reduced pressure at 80°C overnight to obtain polymer (F-7). The yield was 3.7 g. Polymer (H-7) was obtained using polymer (F-7) in the same manner as in Example 1. The ion exchange capacity of polymer (H-7) was measured. The results are shown in Table 1. A mixed solvent of ethanol and water (ethanol / water = 60 / 40 mass ratio) was added to the polymer (H-7) to adjust the solid concentration to 15 mass%, and the mixture was stirred at 105°C for 8 hours using an autoclave to obtain a liquid composition (D-7) in which the polymer (H-7) was dispersed in the dispersion medium.

[0142] [Example 8: Preparation example] In a 125mL stainless steel autoclave, 15.0g of monomer (m22-1), 15.29g of monomer (m12-1), 10.0g of compound (s-1) and 23mg of compound (i-1) were charged and thoroughly degassed under cooling with liquid nitrogen. After that, the temperature was raised to 65°C and stirred for 18 hours, and the autoclave was cooled to stop the reaction. The product was diluted with compound (s-1), n-hexane was added thereto, the polymer was coagulated, and the mixture was filtered. The polymer was then stirred in compound (s-1), re-coagulated with n-hexane, and dried under reduced pressure at 80°C overnight to obtain polymer (F-8). The yield was 12.0 g. Polymer (H-8) was obtained using polymer (F-8) in the same manner as in Example 1. The ion exchange capacity of polymer (H-8) was measured. The results are shown in Table 1. A liquid composition (D-8) was obtained in the same manner as in Example 1 using the polymer (H-8).

[0143] [Example 9: Preparation example] 21.2g of monomer (m11-1), 170g of compound (s-1) and 9.5mg of compound (i-2) were charged into a 230mL stainless steel autoclave and thoroughly degassed under cooling with liquid nitrogen. Then, 20g of TFE was charged, the temperature was raised to 40°C, and the mixture was stirred for 7 hours, after which the autoclave was cooled to stop the reaction. The product was diluted with compound (s-1), n-hexane was added thereto, the polymer was coagulated, and the mixture was filtered. The polymer was then stirred in compound (s-1), re-coagulated with n-hexane, and dried under reduced pressure at 80°C overnight to obtain polymer (F-9). The yield was 11.5 g. Using the polymer (F-9), a polymer (H-9) and a liquid composition (D-9) were obtained in the same manner as in Example 1. The ion exchange capacity of the polymer (H-9) was also measured. The results are shown in Table 1.

[0144] [Example 10: Preparation example] In a stainless steel autoclave with an internal volume of 125 mL, 41.7 g of monomer (m24-1), 31.3 g of monomer (m32-1), and 25.0 mg of compound (i-3) dissolved in compound (s-1) at a concentration of 3.2 mass% were charged, and the mixture was thoroughly degassed under cooling with liquid nitrogen. After that, the mixture was heated to 20°C and stirred for 20 hours, and then the autoclave was cooled to stop the reaction. The product was diluted with compound (s-1), n-hexane was added thereto, the polymer was coagulated, and the mixture was filtered. The polymer was then stirred in compound (s-1), re-coagulated with n-hexane, and dried under reduced pressure at 80°C overnight to obtain polymer (F-10). The yield was 5.9 g. Using the polymer (F-11), a polymer (H-10) and a liquid composition (D-10) were obtained in the same manner as in Example 1. The ion exchange capacity of the polymer (H-10) was measured. The results are shown in Table 1.

[0145] [Example 11: Preparation example] In a stainless steel autoclave with an internal volume of 125 mL, 49.64 g of monomer (m31-4), 28.22 g of compound (s-1), and 38.9 mg of compound (i-3) dissolved in compound (s-1) at a concentration of 3.2 mass% were charged, and the mixture was thoroughly degassed under cooling with liquid nitrogen. The mixture was then heated to 30°C, TFE was introduced into the system, and the pressure was maintained at 0.37 MPaG. After stirring for 4.8 hours, the autoclave was cooled to stop the reaction. The product was diluted with compound (s-1), and then compound (s-2) was added thereto to coagulate the polymer and filter it. The polymer was then stirred in compound (s-1), re-coagulated with compound (s-2), and dried under reduced pressure at 80°C overnight to obtain polymer (F-11). The yield was 15.0 g. Using the polymer (F-11), a polymer (H-11) and a liquid composition (D-11) were obtained in the same manner as in Example 1. The ion exchange capacity of the polymer (H-11) was also measured. The results are shown in Table 1.

[0146] In Table 1, "total content of specific cyclic ether structural units" means the total content (mol %) of the above-mentioned units (u11), (u12), (u21), (u22) and (u24) relative to all units contained in the polymer after hydrolysis treatment.

[0147] [Table 1]

[0148] [Example 12] 67 g of liquid composition (D-1) was added to a mixture of 42 g of water and 36 g of ethanol, and while stirring with a stirrer, mixture A was added so that the carbon alloy catalyst was 20 g, and the solid concentration was adjusted to 22 mass%, to obtain a liquid for forming a catalyst layer. If a large amount of heat was generated during stirring, the mixture was stirred while cooling with a chiller or the like. This liquid was applied to a sheet (trade name: Aflex 100N, manufactured by Asahi Glass Co., Ltd., thickness 100 μm) (hereinafter referred to as ETFE sheet) made of a copolymer of ethylene and TFE prepared separately, dried at 80 ° C for 30 minutes, and further subjected to heat treatment at 160 ° C for 30 minutes to form a catalyst layer.

[0149] The liquid composition (D-11) was applied onto an ETFE sheet using a die coater, dried at 80° C. for 30 minutes, and further subjected to heat treatment at 190° C. for 30 minutes to form a solid polymer electrolyte membrane with a thickness of 17 μm. After peeling off the ETFE sheet from the solid polymer electrolyte membrane, the solid polymer electrolyte membrane was sandwiched between two catalyst layers with ETFE sheets, and hot-pressed under conditions of a press temperature of 160°C, a press time of 5 minutes, and a pressure of 3 MPa. The catalyst layers were bonded to both sides of the solid polymer electrolyte membrane, and the ETFE sheet was peeled off from the catalyst layers to produce an electrode with an area of ​​25 cm. 2 As a result, a membrane electrode assembly of 1000 μm was obtained.

[0150] [Examples 13-22] A membrane / electrode assembly was produced in the same manner as in Example 12, except that the liquid composition (D-1) used to form the catalyst layer was changed to any one of the liquid compositions (D-2) to (D-11).

[0151] [Evaluation test] <Power generation efficiency> Each of the obtained membrane electrode assemblies was assembled into a power generation cell, and the power generation efficiency was evaluated as follows. The temperature of the membrane electrode assembly was maintained at 80°C, and hydrogen (utilization rate 70%) was supplied to the anode, and air (utilization rate 50%) was supplied to the cathode, each pressurized to 150 kPa (absolute pressure). Both hydrogen and air were humidified to a relative humidity of 100% and supplied at a current density of 0.5 A / cm. 2 The cell voltage at this time was recorded. The cell voltage was expressed as an index, with the cell voltage at 0.5 mA of the membrane electrode assembly of Example 22 being set at 1.0. The larger the value, the more excellent the power generation efficiency. The results are shown in Table 2.

[0152] [Table 2]

[0153] As shown in Table 2, it was confirmed that when a carbon alloy catalyst and a catalyst layer containing a polymer having a specific cyclic ether structural unit and an ion exchange group were used (Examples 12 to 21), a fuel cell with excellent power generation efficiency was obtained. The entire contents of the specification, claims, abstract and drawings of Japanese Patent Application No. 2019-237794, filed on December 27, 2019, are hereby incorporated by reference as the disclosure of the specification of the present invention. [Explanation of symbols]

[0154] 10 Membrane electrode assembly 11 Catalyst layer 12 Gas diffusion layer 13 Anode 14 Cathode 15 Solid polymer electrolyte membrane

Claims

1. A carbon alloy catalyst; and a polymer having an ion exchange group, the polymer having at least one unit containing a cyclic ether structure selected from the group consisting of a unit represented by formula (u11), a unit represented by formula (u12), a unit represented by formula (u21), a unit represented by formula (u22), and a unit represented by formula (u24). 【Chemistry 1】 In formula (u11), R 11 is a divalent perfluoro organic group which may have an ether-bonded oxygen atom, R 12 , R 13 , R 15 and R 16 each independently represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom or a fluorine atom; R 14 represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom, a fluorine atom, or -R 11 (SO 2 X (SO 2 R f ) a ) - M + It is a group represented by the following formula: M + H + , a monovalent metal cation or an ammonium ion in which one or more hydrogen atoms may be substituted with a hydrocarbon group; R f is a linear or branched perfluoroalkyl group which may have an ether-bonded oxygen atom, X is an oxygen atom, a nitrogen atom or a carbon atom, and when X is an oxygen atom, a=0; when X is a nitrogen atom, a=1; and when X is a carbon atom, a=2. In formula (u12), R 21 is a perfluoroalkylene group having 1 to 6 carbon atoms or a perfluoroalkylene group having 2 to 6 carbon atoms and an ether-bonding oxygen atom between the carbon-carbon bonds, R 22 represents a fluorine atom, a perfluoroalkyl group having 1 to 6 carbon atoms, a perfluoroalkyl group having 2 to 6 carbon atoms and an ether-bonded oxygen atom between the carbon-carbon bonds, or -R 21 (SO 2 X (SO 2 R f ) a ) - M + It is a group represented by the following formula: M + , R f , X and a are as defined above. In formula (u21), R 41 , R 42 , R 43 , R 44 , R 45 and R 46 each independently represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom or a fluorine atom. In formula (u22), s is 0 or 1; R 51 and R 52 are each independently a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a spiro ring formed by linking together (when s is 0); R 53 and R 54 are each independently a fluorine atom or a perfluoroalkyl group having 1 to 5 carbon atoms; R 55 is a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a perfluoroalkoxy group having 1 to 5 carbon atoms. In formula (u24), R 71 , R 72 , R 73 , R 74 , R 75 and R 76 each independently represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom or a fluorine atom.

2. 2. The catalyst layer according to claim 1, wherein the total content of the units containing a cyclic ether structure is 30 mol % or more based on all units contained in the polymer.

3. The catalyst layer according to claim 1 or 2, wherein the unit containing a cyclic ether structure includes a unit represented by formula (u22).

4. the polymer further comprises units based on a perfluoromonomer, 4. The catalyst layer according to claim 1, wherein the unit based on a perfluoromonomer does not contain a cyclic ether structure and has an ion exchange group.

5. The catalyst layer according to claim 4, wherein the unit based on the perfluoromonomer is a unit represented by formula (u32): 【Chemistry 2】 In formula (u32), Q 1 is a perfluoroalkylene group which may have an ether-bonded oxygen atom, and Q 2 is a single bond or a perfluoroalkylene group which may have an ether-bonded oxygen atom, Y is a fluorine atom or a monovalent perfluoroorganic group, q is 0 or 1, R f is a linear or branched perfluoroalkyl group which may have an ether-bonded oxygen atom, X is an oxygen atom, a nitrogen atom or a carbon atom, and when X is an oxygen atom, a=0; when X is a nitrogen atom, a=1; and when X is a carbon atom, a=2.

6. Catalyst layer according to any one of claims 1 to 5, wherein the ion exchange capacity of the polymer is from 1.1 to 2.8 meq / g dry resin.

7. 7. The catalyst layer according to claim 1, wherein the polymer has a volumetric flux value of from 200 to 330°C.

8. A carbon alloy catalyst; a polymer having at least one unit containing a cyclic ether structure selected from the group consisting of a unit represented by formula (u11), a unit represented by formula (u12), a unit represented by formula (u21), a unit represented by formula (u22), and a unit represented by formula (u24), and having an ion exchange group; A catalyst layer forming liquid comprising: 【Chemistry 3】 In formula (u11), R 11 is a divalent perfluoro organic group which may have an ether-bonded oxygen atom, R 12 , R 13 , R 15 and R 16 each independently represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom or a fluorine atom; R 14 represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom, a fluorine atom, or -R 11 (SO 2 X (SO 2 R f ) a ) - M + It is a group represented by the following formula: M + H + , a monovalent metal cation or an ammonium ion in which one or more hydrogen atoms may be substituted with a hydrocarbon group; R f is a linear or branched perfluoroalkyl group which may have an ether-bonded oxygen atom, X is an oxygen atom, a nitrogen atom or a carbon atom, and when X is an oxygen atom, a=0; when X is a nitrogen atom, a=1; and when X is a carbon atom, a=2. In formula (u12), R 21 is a perfluoroalkylene group having 1 to 6 carbon atoms or a perfluoroalkylene group having 2 to 6 carbon atoms and an ether-bonding oxygen atom between the carbon-carbon bonds, R 22 represents a fluorine atom, a perfluoroalkyl group having 1 to 6 carbon atoms, a perfluoroalkyl group having 2 to 6 carbon atoms and an ether-bonded oxygen atom between the carbon-carbon bonds, or -R 21 (SO 2 X (SO 2 R f ) a ) - M + It is a group represented by the following formula: M + , R f , X and a are as defined above. In formula (u21), R 41 , R 42 , R 43 , R 44 , R 45 and R 46 each independently represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom or a fluorine atom. In formula (u22), s is 0 or 1; R 51 and R 52 are each independently a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a spiro ring formed by linking together (when s is 0); R 53 and R 54 are each independently a fluorine atom or a perfluoroalkyl group having 1 to 5 carbon atoms; R 55 is a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a perfluoroalkoxy group having 1 to 5 carbon atoms. In formula (u24), R 71 , R 72 , R 73 , R 74 , R 75 and R 76 each independently represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom or a fluorine atom.

9. The liquid for forming a catalyst layer according to claim 8 , wherein the total content of the units containing a cyclic ether structure is 30 mol % or more based on all units contained in the polymer.

10. The liquid for forming a catalyst layer according to claim 8 or 9, wherein the unit containing a cyclic ether structure includes a unit represented by formula (u22).

11. the polymer further comprises units based on a perfluoromonomer, The liquid for forming a catalyst layer according to any one of claims 8 to 10, wherein the unit based on the perfluoromonomer does not contain a cyclic ether structure and is a unit having an ion exchange group.

12. The liquid for forming a catalyst layer according to claim 11, wherein the unit based on the perfluoromonomer is a unit represented by formula (u32): 【Chemistry 4】 In formula (u32), Q 1 is a perfluoroalkylene group which may have an ether-bonded oxygen atom, and Q 2 is a single bond or a perfluoroalkylene group which may have an ether-bonded oxygen atom, Y is a fluorine atom or a monovalent perfluoroorganic group, q is 0 or 1, R f is a linear or branched perfluoroalkyl group which may have an ether-bonded oxygen atom, X is an oxygen atom, a nitrogen atom or a carbon atom, and when X is an oxygen atom, a=0; when X is a nitrogen atom, a=1; and when X is a carbon atom, a=2.

13. an anode having a catalyst layer; a cathode having a catalyst layer; a solid polymer electrolyte membrane disposed between the anode and the cathode; A membrane electrode assembly, wherein at least one of the catalyst layer of the anode and the catalyst layer of the cathode is the catalyst layer according to any one of claims 1 to 7.

14. The membrane electrode assembly according to claim 13, which is used in a polymer electrolyte fuel cell.

Citation Information

Patent Citations

  • Solid polymer electrolyte material, liquid composite, solid polymer fuel cell, fluorine-containing polymer and solid polymer electrolyte film consisting of fluorine-containing polymer

    JP2002260705A

  • Gas diffusion electrode and polymer electrolyte fuel cell having its electrode

    JP2003036856A

  • Electrode catalyst for fuel cell and fuel cell using the same

    JP2003249231A

  • Electrode for fuel cell, and its manufacturing method

    JP2004362802A

  • High oxygen-permeable electrolyte, method for producing the same, and sulfonimide monomer

    JP2011140605A